BCG Moreau Polish Substrain Infections in Patients With Inborn Errors of Immunity: 40 Years of Experience in the Department of Immunology, Children's Memorial Health Institute, Warsaw - Bernatowska, Ewa; Pac, Małgorzata; Heropolitańska-Pliszka, Edyta; Pietrucha, Barbara; Dąbrowska-Leonik, Nel; Skomska-Pawliszak, Małgorzata; Bernat-Sitarz, Katarzyna; Krzysztopa-Grzybowska, Katarzyna; Wolska-Kuśnierz, Beata; Bohynikova, Nadia; Augustynowicz, Ewa; Augustynowicz-Kopeć, Ewa; et al. (Frontiers in Pediatrics, 2022)
Objective We aimed to assess BCG (Bacillus Calmette-Guérin) complications in patients with Inborn Errors of Immunity (IEI), according to the inherited disorders and associated immunological defects, as well as the different BCG substrains. Material We studied adverse reactions to the locally-produced BCG Moreau vaccine, analyzed in patients with IEI diagnosed between 1980 and 2020 in the Department of Immunology, Children's Memorial Health Institute (CMHI), Warsaw. These results were compared with previously published studies. Results Significantly fewer disseminated BCG infections (BCGosis) were found in 11 of 72 (15%) SCID (Severe Combined Immunodeficiency) NK (Natural Killer)-phenotype patients, when compared with the 119 out of 349 (34%) (p = 0.0012) patients with SCID with BCG in other countries. Significantly fewer deaths caused by BCGosis were observed (p = 0.0402). A significantly higher number of hematopoietic stem cell transplantations (HSCTs) were performed in the CMHI study (p = 0.00001). BCGosis was found in six patients with Mendelian susceptibility to mycobacterial diseases (MSMD). Other patients with IEI prone to BCG complications, such as CGD (Chronic Granulomatous Disease), showed no case of BCGosis. Conclusion The BCG Moreau substrain vaccine, produced in Poland since 1955, showed genetic differences with its parental Brazilian substrain together with a superior clinical safety profile in comparison with the other BCG substrains, with no BCGosis in patients with IEI other than SCID and MSMD. Our data also confirmed significantly fewer cases of BCGosis and deaths caused by BCG infection in patients with SCID with this vaccine substrain. Finally, they confirmed the protecting role of NK cells, probably via their production of IFN-γ.